A Multichannel Oscillator for a Resonant Chemical Sensor System - Lee, Hyunjoo Jenny; Park, Kwan Kyu; Oralkan, Omer; Kupnik, Mario; Khuri-Yakub, Butrus T. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
Vapor detection using highly sensitive miniaturized resonant sensors is of great interest for many applications, including consumer, industrial, and environmental applications. An operational-amplifier-based multichannel oscillator that interfaces with a 50-MHz capacitive micromachined ultrasonic transducer array is presented for chemical sensing applications. The circuit was implemented in a 0.18-mu m CMOS technology to reduce power consumption, number of wires, and active area per channel. The presented integrated circuit also addresses the potential-frequency-locking problem between channels by allowing the open-loop gain to be adjustable off-chip. The feasibility of the developed oscillator for the chemical sensing application is demonstrated. Two channels that were operated simultaneously achieved excellent volume sensitivities of 8.5 x 10(-4)%/Hz and 3.9 x 10(-4)%/Hz, respectively, to relative humidity in N-2.
Keywords: MESOPOROUS SILICA; QUALITY FACTOR; PHASE NOISE; CO2; DESIGN; ARRAY